2013
DOI: 10.1155/2013/867893
|View full text |Cite
|
Sign up to set email alerts
|

Boehmeria niveaStimulates Glucose Uptake by Activating Peroxisome Proliferator-Activated Receptor Gamma in C2C12 Cells and Improves Glucose Intolerance in Mice Fed a High-Fat Diet

Abstract: We examined the antidiabetic property of Boehmeria nivea (L.) Gaud. Ethanolic extract of Boehmeria nivea (L.) Gaud. (EBN) increased the uptake of 2-[N-(nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy-d-glucose in C2C12 myotubes. To examine the mechanisms underlying EBN-mediated increase in glucose uptake, we examined the transcriptional activity and expression of peroxisome proliferator-activated receptor gamma (PPAR-γ), a pivotal target for glucose metabolism in C2C12 myotubes. We found that the EBN increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…It is thought that RLE rich in dietary fiber may shorten intestinal transit time, leading to the decreased number of fecal pellets in the colon. In addition, these results were similar to those of previous reports (Attaluri et al, 2011;Han et al, 2017;Kakino et al, 2010;Kim, Lee, et al, 2013;Kim, Sung, et al, 2013;Kim et al, 2018;Méité et al, 2010;Sathyanathan et al, 2013;Seo et al, 2013). Méité et al (2010) reported that Mareya micrantha (Benth.)…”
Section: Ta B L Esupporting
confidence: 92%
See 2 more Smart Citations
“…It is thought that RLE rich in dietary fiber may shorten intestinal transit time, leading to the decreased number of fecal pellets in the colon. In addition, these results were similar to those of previous reports (Attaluri et al, 2011;Han et al, 2017;Kakino et al, 2010;Kim, Lee, et al, 2013;Kim, Sung, et al, 2013;Kim et al, 2018;Méité et al, 2010;Sathyanathan et al, 2013;Seo et al, 2013). Méité et al (2010) reported that Mareya micrantha (Benth.)…”
Section: Ta B L Esupporting
confidence: 92%
“…These findings were also similar to Wintola et al (2010). Food intake and water consumption are considered important factors for the assessment of constipation symptoms and therapeutic effects (Kim, Lee, et al, 2013;Kim, Sung, et al, 2013). In our study, food intake and water consumption increased in response to RLE treatment after constipation induction.…”
Section: Ta B L Esupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with previous studies, we found that Boehmeria nivea leaves contained abundant polyphenol components. Recent studies have shown that BNE exerts anti-inflammatory [ 6 ], antioxidant [ 15 ], anti-hepatitis B virus [ 5 ], anti-colitis [ 7 ], anti-obesity [ 20 ], and anti-diabetic effects [ 21 ]. Based on these known effects, we assumed that BNE might play a role in suppressing IgE-mediated mast cell inflammation and could be used for treating allergic diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the type 2 diabetes, there are crucial molecules that could be therapeutic targets for the treatment of type 2 diabetes. Peroxisome proliferator‐activated receptor gamma (PPAR‐ γ ) is responsible for glucose uptake and regulation of fatty acid, and PPAR‐ γ agonists have been wildly used for the treatment of diabetes (Kim et al , ). In addition, insulin receptor subunit‐1 (IRS‐1) is a trigger molecule to transmit the insulin signaling to downstream molecules (Draznin, ).…”
Section: Introductionmentioning
confidence: 99%